간호대학생의 건강정보이해능력 역량, 비판적 사고성향 및 윤리적 민감성이 환자중심 간호역량에 미치는 영향 - 고미숙; Ko, Mi Suk (근관절건강학회지, 2025)
Purpose: This study explored factors that influence patient-centered care competency in nursing students. Methods: Data were collected from 184 nursing students at three university in Seoul, Gyeonggi Province, and Gangwon Province. Data were analyzed in SPSS 29.0 using descriptive statistics, t-tests, one-way ANOVA, Pearson correlation coefficients, and multiple regression analysis. Results: Nursing students obtained an above-average score (3.54 points) in patient-centered care competency. There were significant differences in sex, religion, and satisfaction with major. Patient-centered care competency was positively correlated with health literacy competency (r=.58, p<.001) and critical thinking disposition (r=.36, p<.001) but was not significantly correlated with ethical sensitivity. Factors that had an patient-centered care competency included Health literacy competency (β=.50, p<.001) significantly impacted patient-centered care competency explaining 36.0% of the effect. Conclusion: To improve nursing students' patient-centered competency, it is necessary to systematically develop and a program that can cultivate the knowledge, skills, and attitudes associated with health literacy competency.